Automated random colour keypad. (23rd September 2019) - Abhishek, Kumar; Verma, Manish Kumar; Singh, Maheshwari Prasad
In early 1970s, automated teller machine came into existence which was placement for cash counters at banks. People could now do transactions 24X7 with ease. But as ATM expanded its reach into human life, crimes related to ATM theft and fraud increased exponentially. There are flaws related to ATM security which is exploited by the criminals. ATM card cloning, card skimming, ATM pin theft are few of the most common crimes related to the ATM. These crimes result in loss of money measured in billions. The newspapers are full of these crime reports and hacks. In this paper, we have proposed an automated random colour keypad by which ATM security can be enhanced; making these ATM attacks and fraud very difficult. This ARC keypad will act as a secure replacement for traditional ATM keypad. Several experimental results of the ARC keypad have been included in this paper which proves that our mechanism enhances ATM pin security and reduces the chances of fraud to a great extent.